2002
DOI: 10.1080/10575630290020622
|View full text |Cite
|
Sign up to set email alerts
|

Partial Synthesis of 23-Hydroxyursolic Acid Isolated from Medicinal Plants of the Rubiaceae Family

Abstract: 23-Hydroxyursolic acid (2), previously isolated from medicinal plants of the Rubiaceae family, was synthesized in ten steps via methyl 23-hydroxy-3-oxours-12-en-28-oate (5) from commercially available ursolic acid (6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…23-OHUA extracted from Lagerstroemia speciosa and Juglans sinensis 19 , has been shown to be an effective anticancer compound 18, 26 , but data on its potential anti-inflammatory properties is limited. With the exception of an additional hydroxyl group in position 23, 23-OHUA has the same structure as UA, which explains why 23-OHUA appears to function through the same molecular mechanisms as UA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23-OHUA extracted from Lagerstroemia speciosa and Juglans sinensis 19 , has been shown to be an effective anticancer compound 18, 26 , but data on its potential anti-inflammatory properties is limited. With the exception of an additional hydroxyl group in position 23, 23-OHUA has the same structure as UA, which explains why 23-OHUA appears to function through the same molecular mechanisms as UA.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicate that UA and 23-OHUA may act through a similar pathway and that 23-OHUA, like UA, may be atheroprotective. 23-OHUA has been extracted from various medicinal herbs and studied for its anti-cancer effects 18, 19 , but its therapeutic properties in the context of metabolic diseases and chronic inflammatory diseases are unknown. We, therefore, examined whether 23-OHUA at physiological relevant doses protects mice against atherosclerosis and its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial aim was the hydroxylation of the hindered C-4 equatorial methyl group of methyl oleanate ( 3 ). This functionalization was achieved according to Baldwin's method, which involves cyclopalladation of the methyl group from a 3-oxime functionality . Thus, the oxidation of methyl oleanate yielded the 3-oxoderivative 5 that was oximated to give methyl oleanate 3-oxime 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on structure-function studies using ursolic acid and nine of its naturally occurring UA analogues, Nguyen et al identified 23-hydroxy ursolic acid (23-OH UA) as a novel, naturally occurring triterpenoid with potential health benefits [ 19 ] ( Table 3 ). 23-OH UA is a phytochemical found in the leaves of Lagerstroemia speciosa or giant crepe-myrtle native to South East Asia, and leaves and twigs of Juglans sinensis, a walnut tree found in East Asia [ 141 ]. Like UA, 23-OH UA prevented nutrient-stress induced dysfunction in THP-1 monocytic cells and human blood monocytes.…”
Section: Biological Effects Of Naturally Occurring Analogues Of Uamentioning
confidence: 99%